ENGLISH TEACHERS’ PROBLEMS IN THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN CURRICULUM 2013 - Arienda, Della; Sofian, Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this study was to describe the problems in the implementation of scientific approach to teach English in SMKN 1 Pontianak. The design of this research is a descriptive study. The subject of this research was two English teachers who teach tenth-grade students of SMKN 1 Pontianak in academic year 2017/2018 who mentioned as first and second informant. In collecting the data, the researcher used semi-structured interviews, classroom observations, and documents study. The findings showed that the implementation was not completely in line with the standard of Ministry of the Education and Culture. Problems occurred in all stages of scientific approach; observing, questioning, experimenting, associating, and networking. The teachers faced problems in creating creative observation activities, encouraging students to ask, designing appropriate task, engaging students to be active in discussions, and giving feedback after students’ presentation. These problems happened because of some factors; time management, lack of facilitation, students’ level of competence, and human resource knowledge itself. Both of the teachers did not pay attention to these factors while designing the task for experimenting activity. The second informant could implement these stages better than the first one. It happened because she has had training.Keywords: Teachers’ Problems, Scientific Approach, Curriculum 2013